PROFIL KEMAMPUAN LITERASI MATEMATIKA DITINJAU DARI GAYA BELAJAR - Nuril Khusniyah; Ana Rahmawati; Dian Novita Rohmatin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Learning style is a method used by each individual to absorb information easily and quickly. Learning style is one of the supporting factors related to mathematical literacy ability. This can happen because learning styles can affect learning outcomes and student achievement. In this study, the learning style used is the VAK learning style (Visual, Audiotori, Kinesthetic). The purpose of this research is to describe how students' mathematical literacy skills at VAK learning style. Selected 1 student who has the highest score on the visual learning style, 1 student who has the highest score on the auditory learning style, and 1 student who has the highest score on the kinesthetic learning style. The results obtained from this study are students with the highest visual learning style can complete level 1 correctly. at level 3 and 4 students with the highest visual learning style came to the indicators of translating problems. Meanwhile, students with the highest auditory learning style were only able to complete level 3 correctly. Meanwhile, students with the highest kinesthetic learning style can complete level 1 correctly. At level 3 only errors occur when drawing conclusions. So it can be concluded that students with the highest visual learning styles can achieve higher competencies than students with auditory and kinesthetic learning styles.